Testing the Speaking Ability at Oral Exams in Departments of English Studies - Jedynak, Małgorzata (Baltic Journal of English Language, Literature and Culture, 2013)
The paper discusses the problem of assessing spoken English production starting from the theoretical deliberations on testing the communicative ability. In the empirical part, the author reports on the two approaches to testing the students’ oral performance at the final oral examinations in the Departments of English Studies at the University of Wrocław and the Higher Vocational School in Nysa, both located in the south-west of Poland. The impact of preparation time, the examination format, and testing techniques on the students’ oral performance were investigated in a qualitative study. Being an examiner the author examined the oral material collected during the two final examinations in the above mentioned Departments. The findings show that the two approaches to oral performance testing have an influence on the students’ productions. The paper concludes with some recommendations for the examiners related to the introduction of a more complex testing system in which a versatile student-student and student-teacher format and at least two different testing techniques are used. Additionally, the allocation of a relatively short time for students to prepare at an oral examination is advocated for enhancing natural everyday communication which is a priority in the currently dominant communicative approach to foreign language learning and teaching.